TINJAUAN HUKUM EKONOMI SYARIAH TERHADAP MEKANISME PENGUPAHAN PEKERJA TANAM PADI PADA TRADISI “NYOMAK” DI DESA KOTANEGARA KECAMATAN MADANG SUKU II KABUPATEN OKU TIMUR - Sutanto, Muhammad Agus; Atika, Atika; Himsyah, Fatroyah Asr (Muamalah, 2020)
ABSTRACT Ji'alah is a certain reward agreement from the first party to the second party for the implementation of a task / service performed by the second party for the benefit of the first party. Likewise with the custom that applies to the people of Kotanegara Village, Madang Tribe II District, East OKU Regency, they often hold wage transactions for rice planting workers using the Komering tribe tradition, namely Nyomak. Starting from this discussion, the main issues to be discussed include how the wage mechanism of rice planting workers in the nyomak tradition and the reasons behind the wage mechanism in the nyomak tradition, how is the review of Islamic law on the wage mechanism in the nyomak tradition. This research is field research (field research). This research is field research (field research). The data collection used in this study were interviews, observation and documentation. This study uses a qualitative descriptive analysis method. Judging from the implementation of the transaction which in this case can be seen in the fulfillment of the pillars and conditions, there are still those that are not in accordance with the provisions of the syara '. This is because the implementation of wages in the nyomak tradition still contains mudhaarat rather than benefits. Mudhaarat in wages using the nyomak tradition lies in the distribution of the final product which is still not in accordance with the initial agreement to share the rice harvest. The kemudharatan contained in this mechanism contradicts one of the principles of the contract in Sharia Economic Law, namely luzum / unchanging, every contract is carried out with clear objectives and careful calculations, in order to avoid speculation or maysir practices, so that the conclusion is the wage mechanism in the nyomak tradition. according to fiqh it should not be done. Keyword: Nyomak tradition, Ji'alah (wage), Sharia Economic Law.